PENERAPAN ALAT PERAGA SERI-PARALEL DC UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI HUKUM OHM - Galuh Ayu Riyanti; Sutikno Sutikno; Masturi Masturi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The aim of this study is to find out the use of series-paralel DC demonstrating tools to improve students’ understanding in Ohm law. This study uses Pre-Experimentalwith One-Group Pretest-Posttest design. The population used was all XI grade students of a vocational school in Pemalang regency in the academic year of 2014-2015. The sample of the study were students of class XI TP 1 who were taken accordingly by purposive sampling. The tecniques used were observation, test, and interview. The result shows that the use of series-paralel DC demonstrating tools can improve students’ understanding in Ohm law. Keywords : Demonstrating tools; Ohm law; Understanding.